The Political Economy of Privatization. Why Do Governments Want Reforms? - Kira Börner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
International organizations promote privatization as precondition for economic development. But is there really too little privatization? This political economy model asks for the incentives of governments to privatize or restructure a state-owned firm. Different government types are compared to identify the political and institutional determinants of privatization. Under privatization, governments commit not to influence the profit-maximizing employment choice by private investors. With respect to the social optimum, both voter-oriented and egoistic governments can have inefficiently high incentives to privatize. When this is the case, outside pressure to privatize is detrimental. An improving institutional environment reduces these inefficiencies.
urn:nbn:de:bvb:19-epub-296-1
Keywords: D72; D73; H82; L33; 330; political incentives; privatization; restructuring; employment